2018
DOI: 10.1016/s0140-6736(18)31615-5
|View full text |Cite
|
Sign up to set email alerts
|

Promoting school climate and health outcomes with the SEHER multi-component secondary school intervention in Bihar, India: a cluster-randomised controlled trial

Abstract: Promoting school climate and health-related outcomes: a cluster randomised controlled trial of the SEHER multi-component secondary school intervention in Bihar, India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
121
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(204 citation statements)
references
References 39 publications
4
121
0
2
Order By: Relevance
“…Sufficient coordination and communication at the school level, the availability of external PE, team cohesion, and feedback loops among all actors involved enhanced the implementation of the changes. These findings of the current study, in which we used a systems approach, are consistent with and add to the findings and recommendations of previous studies which also point to the importance of feedback, external support, clear coordination and communication, and bottom-up involvement for sufficient adoption and implementation of school health promotion programmes [20,95,96,101]. The current study further extends the knowledge by, among other things, insight on creating disruption in the schools.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Sufficient coordination and communication at the school level, the availability of external PE, team cohesion, and feedback loops among all actors involved enhanced the implementation of the changes. These findings of the current study, in which we used a systems approach, are consistent with and add to the findings and recommendations of previous studies which also point to the importance of feedback, external support, clear coordination and communication, and bottom-up involvement for sufficient adoption and implementation of school health promotion programmes [20,95,96,101]. The current study further extends the knowledge by, among other things, insight on creating disruption in the schools.…”
Section: Discussionsupporting
confidence: 91%
“…Even though this favourable effect on children's BMI zscore seems promising, the effect can be indicated as a small effect, according to Lipsey's guidelines [100], and therefore raises the question regarding its clinical relevance. Previous studies have explored the minimal differences in BMI-z scores in overweight children to ensure clinically relevant health benefits [101]. As yet, little is known about when population-level public health interventions achieve clinical relevance [165].…”
Section: Clinical Relevance Of the Effects Of Hpsf On Children's Healmentioning
confidence: 99%
“…We previously reported strong effects of the SEHER intervention on school climate, violence and bullying, depression and attitude towards gender norms after one academic year of exposure, and dose-response effects after two years, in the SM arm of the trial. On the other hand, there was no evidence of an intervention effect on any outcome either after one or two years of intervention in the TSM arm [9][10].…”
Section: Box 1: Overview Of the Seher Trialmentioning
confidence: 70%
“…Comparison schools received the Adolescence Education Program (AEP), a classroom-delivered life-skills curriculum, which was conducted in all schools in all arms. Full details of the intervention and the evaluation have been reported elsewhere [8][9][10]. Box 1 provides an overview of the SEHER interventions and trial.…”
mentioning
confidence: 99%
“…A trial of a multi-level, structural and norms-based intervention in Karnataka found no evidence of a reduction in school drop-out and child marriage among girls aged 12-13 [34]. The whole-school SEHER (Strengthening Evidence base on scHool-based in-tErventions for pRomoting adolescent health programme) intervention delivered by lay counsellors in Bihar improved school climate and health-related outcomes among secondary school students (including depression, bullying and violence victimisation) [35].…”
Section: Discussionmentioning
confidence: 99%